Sheep Farmers in the Realm of Læstadius: Science and Religion as Motivating Forces in the Community of Practice in Northern Norway - Lillevoll, Tor Arne (Journal of Northern Studies, 2017)
The article discusses some aspects of a successful development in a village in Northern Norway, where agriculture is an important industry. The author examines family-based farms with sheep, upbringing, socialization and learning in communities of practice, and integrated academic and sociocultural forces in development. Sheep farming in the studied village is integrated into a sophisticated field of knowledge rooted in the local culture. An important aspect is the bidirectional support and knowledge exchange between experience-based and science-based knowledge centres (i.e. there is a two-way transfer): the farmers supply external agricultural experts with data on breeding and fattening, and subsequently input their derived knowledge for further use in development. Another important part of this field of practice is financial support from the state. The author argues that the interaction between culture and the business environment is important and provides synergy. As a consequence, an extraordinary momentum resulting from sheep farming is created in the mapping between the organized business community on the one hand, and local culture and religious communities with strong historical roots on the other hand. The findings indicate that these conditions could be of general interest for innovation and development also in other industries and other types of societies.